1991
DOI: 10.2307/3869202
|View full text |Cite
|
Sign up to set email alerts
|

Macrostructure of the Tomato Telomeres

Abstract: The macrostructure of the tomato telomeres has been investigated by in situ hybridization, genomic sequencing, and pulsed-field gel electrophoresis. In situ hybridizations with a cloned telomeric sequence from Arabidopsis thaliana indicated that the telomeric repeat of tomato cross-hybridizes with that of Arabidopsis and is located at all telomeres. Ba131 digestion kinetics confirmed that the tomato telomeric repeat represents the outermost DNA sequence of each tomato chromosome. Genomic sequencing of enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…FISH showed that this repeat is present in the heterochromatin of all pericentromeres, but not in the nucleolar organizer regions (NORs) (Zhong et al 1996). Three major genomic repeats, TGRI, TGRII and TGRIII, were described by Schweizer et al (1988), Ganal et al (1988Ganal et al ( , 1991 and Lapitan et al (1989Lapitan et al ( , 1991. It was shown that TGRI is located in the distal regions, and that TGRII and TGRIII are located in the pericentromere heterochromatin regions of the chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…FISH showed that this repeat is present in the heterochromatin of all pericentromeres, but not in the nucleolar organizer regions (NORs) (Zhong et al 1996). Three major genomic repeats, TGRI, TGRII and TGRIII, were described by Schweizer et al (1988), Ganal et al (1988Ganal et al ( , 1991 and Lapitan et al (1989Lapitan et al ( , 1991. It was shown that TGRI is located in the distal regions, and that TGRII and TGRIII are located in the pericentromere heterochromatin regions of the chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, for example, the telomeric repeats are associated with the TGRI satellite repeat at 20 of the 24 chromosome ends, and the distance between the two repeated sequences ranges from a few bp to 150 kb of spacer DNA [1]. Our recent PFGE study on tobacco chromosomes [4] has shown a similar long-range organization of their termini.…”
Section: Introductionmentioning
confidence: 99%
“…The ends of eukaryotic chromosomes consist of many tandemly repeated copies of a DNA sequence (T/A)t.4G ~ 8 [1]. In plants, telomeric sequences were first cloned and sequenced in Arabidopsis thaliana [2].…”
Section: Introductionmentioning
confidence: 99%
“…The human-type telomere repeat (TTAGGG) n is common in vertebrates (Meyne et al 1989), and it has also been reported in some protozoa and fungi (Blackburn and Gall, 1978, Blackburn and Challoner, 1984, Schechtman, 1990. In plants, the telomere repeat (TTTAGGG) n was isolated in Arabidopsis Ausubel 1988, Richards et al 1992), and this Arabidopsis-type repeat has been reported in many angiosperms and gymnosperms (Ganal et al 1991, Broun et al 1992, Cox et al 1993, Biessmann and Mason 1994, Fuchs et al 1995, Wellinger and Sen 1997, Hizume et al 1998. Allium cepa and A. fistulosum possess unique terminal repetitive sequences and/or rDNA sequences in place of the typical telomere sequence (Pich et al 1996, Pich andSchubert 1998), and the absence of Arabidopsis-type telomere repeats were reported in other Asparagales (Adams et al 2000(Adams et al , 2001.…”
mentioning
confidence: 99%